Audit Committee Characteristics and Firm Performance: Evidence from Malaysian Finance Companies - Al-Matari, Yahya Ali; Al-Matari, Ebrahim Mohammed; Homaid, Abdo Ali (2017)
This study examined the effect of audit committee characteristics including competence of the audit committee members, the member of the professional body, and the frequency of audit committee meetings, on the finance companies performance.The study was conducted involving 33 companies that were included in the list of the Bursa Malaysia, covered in the period from 2011-2015, a total of 165 firmyears observations. The study made use of Pearson Correlation Coefficient and Multiple Regressions analysis.The findings revealed that the variables of audit committee independence, audit committee finance literacy and Audit committee member of accounting professional body influence significantly the performance of finance companies.Specifically, audit committee finance literacy has been found to be the most positively significant variable to influence finance companies performance. However, audit committee size may not contribute to enhancing finance companies performance. Moreover, this study conducted a review of literature relevant to the topic of audit committee characteristics and it presented practical implications as well as suggestions that future studies can follow.